Gadolinium tissue deposition in the periodontal ligament of mice with reduced renal function exposed to Gd-based contrast agents. - Delfino, Riccarda; Biasotto, Matteo; Candido, Riccardo; Altissimo, Matteo; Stebel, Marco; Salomè, Murielle; van Elteren, Johannes T; Vogel Mikuš, Katarina; Zennaro, Cristina; Šala, Martin; Addobbati, Riccardo; Tromba, Giuliana; et al. (Toxicol Lett, 2019)
Gadolinium deposition in tissue is linked to nephrogenic systemic fibrosis (NSF): a rare disorder occurring in patients with severe chronic kidney disease and associated with administration of Gd-based contrast agents (GBCAs) for Magnetic Resonance Imaging (MRI). It is suggested that the GBCAs prolonged permanence in blood in these patients may result in a Gd precipitation in peripheral or central organs, where it initiates a fibrotic process. In this study we investigated new sites of retention/precipitation of Gd in a mouse model of renal disease (5/6 nephrectomy) receiving two doses (closely after each other) of a linear GBCA. Two commercial GBCAs (Omniscan® and Magnevist®) were administered at doses slightly higher than those used in clinical practice (0.7 mmol/kg body weight, each). The animals were sacrificed one month after the last administration and the explanted organs (kidney, liver, femur, dorsal skin, teeth) were analysed by X-ray fluorescence (XRF) at two synchrotron facilities. The XRF analysis with a millimetre-sized beam at the SYRMEP beamline (Elettra, Italy) produced no detectable levels of Gd in the examined tissues, with the notable exception of the incisors of the nephrectomised mice. The XRF analyses at sub-micron resolution performed at ID21 (ESRF, France) allowed to clearly localize Gd in the periodontal ligaments of teeth both from Omniscan® and Magnevist® treated nephrectomised mice. The latter results were further confirmed by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The study prompts that prolonged permanence of GBCAs in blood may result in Gd retention in this particular muscular tissue, opening possibilities for diagnostic applications at this level when investigating Gd-related toxicities.
Keywords: Animals; Contrast Media; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gadolinium; Gadolinium DTPA; Magnetic Resonance Imaging; Mice; Nephrogenic Fibrosing Dermopathy; Periodontal Ligament; Renal Insufficiency; Tissue Distribution